Once more we saw stars - Greene, Jayson (Alfred A. Knopf, 2019)
"Two-year-old Greta Greene was sitting with her grandmother on a park bench on the Upper West Side of Manhattan when a brick crumbled from a windowsill overhead, striking her unconscious. She is immediately rushed to the hospital. Once More We Saw Stars begins with this event, leading the reader into the unimaginable. But although it begins with the anguish Jayson and his wife Stacy confront in the wake of their daughter's trauma and the hours leading up to her death, it quickly becomes a narrative that is as much about hope and healing as it is about grief and loss. Jayson recognizes, even in the very midst of his ordeal, that there will be a life for him beyond it--that if only he can continue moving forward, from one moment to the next, he will survive what seems un-survivable. With raw honesty, deep emotion, and exquisite tenderness, he captures both the fragility of life and absoluteness of death, and most important of all, the unconquerable power of love. This is an unforgettable memoir of courage and transformation - and a book that will change the way you look at the world"--